Historical Polarization and Representation in South American Party Systems, 1900–1990. Issue 1 (5th December 2016) - Bornschier, Simon
Abstract : Although ideological polarization can create problems for governability and democratic stability, this article argues that it also has beneficial effects in new democracies. By clarifying the political alternatives, polarization creates strong links between parties and voters, and thereby instills accountability mechanisms that force parties to remain responsive to evolving voter preferences. A comparative historical analysis of six South American cases demonstrates that the vast differences in the quality of representation in the 1980s, immediately after many countries in the region returned to democracy, were rooted in an early bifurcation of party systems in the first half of the twentieth century: while prolonged periods of ideological conflict occurred in some countries during this period, polarization was aborted by various means in others. By showing that ideological moderation may help formal democracies survive, but that aborting conflict in the long run severely hampers key aspects of the quality of democracy, this study suggests a revision of conventional views regarding ideological polarization.